Multivariate Drought Monitoring, Propagation, and Projection Using Bias‐Corrected General Circulation Models. Issue 4 (25th April 2023) - Adeyeri, Oluwafemi E.; Zhou, Wen; Laux, Patrick; Ndehedehe, Christopher E.; Wang, Xuan; Usman, Muhammad; Akinsanola, Akintomide A.
Abstract: Understanding how droughts are characterized, propagated, and projected, particularly multivariate droughts, is necessary to explain the variability and changes in drought characteristics. This study aims to understand multimodel global drought monitoring, propagation, and projection by utilizing a multivariate standardized drought index (MSDI) during the historical (1959–2014) and future (2045–2100) periods under two socioeconomic pathways SSPs (370 and 585), derived from the bias‐corrected Coupled Model Intercomparison Project Phase 6 (CMIP6). Based on the energy metrics, the multivariate bias correction method outperformed other techniques in correcting the biases in the CMIP6 drought representation. The drought indicators demonstrate distinct categories for meteorological, hydrological, and multivariate droughts. There were significant high cross correlations between Heatwave Total Length (HWTL) and MSDI in Africa and South America for all lagged times. Europe and North America generally saw the maximum MSDI drought duration (228 months) during the historical period. For future projections, Africa recorded the maximum drought duration (197 months), while Europe witnessed the minimum drought duration for SSP 370 (171 months), and North America (149 months) for SSP 585. Furthermore, during the historical period in tropical Africa, the propagation of meteorological to hydrological drought was slower during the wet months than during the dry months. Under the SSP 370 future projection, there was a shift in the long period of meteorological‐hydrological propagation from the middle and late wet months to the beginning of the wet months in tropical Africa. Therefore, tracking and projecting drought characteristics is vital for understanding the risk of drought‐related consequences. Plain Language Summary: This study investigates a multimodel approach to assessing the global drought and learning more about how droughts spread, are predicted, what they look like, and their effects. Depending on the time of year, the beginning of a hydrological and multivariate drought differs from that of a meteorological drought. In general, under the medium and high socioeconomic and carbon emission scenarios, drought severity and intensity increased from the historical period to the end of the 21st century. Africa had the longest drought at the end of the 21st century (197 months). In contrast, under the medium socioeconomic and carbon emission scenarios, Europe experienced the shortest drought duration (171 months). In midlatitude Europe, the transition from a meteorological to a hydrological drought occurred slowly over the peak winter and spring months. In late summer and early fall, heatwave took an average of 1 month to propagate into hydrological drought. Future droughts are expected to be more severe for most continents. This suggests more prevalent future droughts, increasing the vulnerability of more nations to the consequences of climate change. Therefore, while creating drought preparedness, adaptation, or mitigation strategies, policymakers and planners must simultaneously consider the impacts of drought on multiple subsystems, drought propagation qualities, and regional exogenous conditions. Key Points: Multivariate bias correction technique performed best in correcting general circulation model biases Meteorological to hydrological drought propagation was slower during the wet months in tropical Africa Multivariate Standardized Drought Index (MSDI) accurately captured previous drought episodes on several continents